Forester and Chemist-Partners - Bruner, M. H. (Indian Forester, 1946)
This article by a forester and Senior Member of the society of American Foresters emphasizes the importance of wood as one of the basic raw materials of industrial chemistry. Through the development of new and improved products, numerous examples of which are cited, the chemist is enabling the forests to contribute more fully to our well-being and is at the same time providing increased incentive for their better management. An expanded and dynamic programme of research is needed to insure still further progress in this field, which offers one of the most promising means of strengthening the hands of the forester by creating a profitable outlet for products and more particularly the by-roducts, of his efforts.